1981
DOI: 10.1346/ccmn.1981.0290402
|View full text |Cite
|
Sign up to set email alerts
|

Burial and Contact Metamorphism in the Mancos Shale

Abstract: Abstract--Clay samples from shales and bentonites in the Mancos Shale (Cretaceous) and its stratigraphic equivalents in the southern Rocky Mountain and Colorado Plateau have been analyzed by X-ray powder diffraction methods. The major clay in the shales is mixed layered illite/smectite, with 20-60% illite layers. The regional distribution of ordered vs. random interstratification in the illite/smectite is consistent with the concept of burial metamorphism in which smectite intedayers are converted to illite, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
4

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 36 publications
5
75
1
4
Order By: Relevance
“…Using the nomograph of Sweeney and Bumham (1990, their Figure 5) and measured VRo's, these rocks are tentatively projected as heated between 100-125~ significantly reducing microbial populations. Thermophiles, however, may have survived these temperatures, Lastly, although significant amounts of illite were not formed outside the metamorphic aureole because of the emplacement of Cerro Negro, the formation of illite in shales in proximity to intrusions is documented elsewhere in the Western Interior Basin (e.g., Nadeau and Reynolds, 1981;Pytte, 1982;Pytte and Reynolds, 1989). For example, diagenetic illite was formed in shales and bentonites more than 1 km away from the Cerrillos Intrusion (Nadeau and Reynolds, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Using the nomograph of Sweeney and Bumham (1990, their Figure 5) and measured VRo's, these rocks are tentatively projected as heated between 100-125~ significantly reducing microbial populations. Thermophiles, however, may have survived these temperatures, Lastly, although significant amounts of illite were not formed outside the metamorphic aureole because of the emplacement of Cerro Negro, the formation of illite in shales in proximity to intrusions is documented elsewhere in the Western Interior Basin (e.g., Nadeau and Reynolds, 1981;Pytte, 1982;Pytte and Reynolds, 1989). For example, diagenetic illite was formed in shales and bentonites more than 1 km away from the Cerrillos Intrusion (Nadeau and Reynolds, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…A plot laased on Figure 1 and calibrated for the percentage ofsmectite layers with the computer-calculated data ( Figure 2) serves for precise measurement of the illite/smectite ratio in highly illitic mixed-layer min- Drits and Sakharov (1976) and Nadeau and Reynolds (1981) is not introduced for reasons discussed below. To make a determination from Figure 2, one must plot the experimental values of the 002 and 003 reflections and read the percentage of smectite by interpolation between the appropriate lines.…”
Section: Thickness Of the Illite Layer And The Refined Technique For mentioning
confidence: 99%
“…The KIs around small (< 10 m) intrusions were anomalously high (Fig. 5), in contrast to the increase degree of crystallinity expected by Nadeau and Reynolds (1981). The aureole is a few millimeters thick, so the KI might be expected to reflect higher crystallinity near this area (assuming temperature to be the most important factor).…”
Section: Resultsmentioning
confidence: 89%
“…These metapelites are intruded by many contemporaneous rhyolite and dolerite intrusions; the effect of these intrusions on KI is not established in the literature. Effects of proximity to an igneous intrusion on illite-smectite (I-S) mineralogical variation were described by Nadeau and Reynolds (1981), who found that close to the intrusion the I-S is markedly more ordered than far away from it and that the percentage of illite layers in the I-S close to the intrusion is markedly larger. They noted that the I-S changes from random to ordered interstratification between the 100º and 150ºC isotherm at about 5 km from the intrusive centre.…”
Section: Introductionmentioning
confidence: 99%